Psychology 2010 : the psychology of human development. Lecture 14. Preschool experience - Memorial University of Newfoundland. Educational Television Centre; Peterson, Carole, 1942-; Strawbridge, Jack (Memorial University of Newfoundland. Educational Television Centre, 1982)
Dr. Jack Strawbridge examines preschool experience. It includes screening an episode of The Growing Years (Coast Community College District, 1977) entitled "The Preschool Experience," followed by an interview with Melba Rabinowitz of the Daybreak Parent Child Center in St. John's. Joint instructors: Dr. Carole Peterson and Dr. Jack Strawbridge. Missing lectures 8-11. Minor distortion throughout.